2018
DOI: 10.1021/acs.jpca.8b06611
|View full text |Cite
|
Sign up to set email alerts
|

Rovibrational Considerations for the Monomers and Dimers of Magnesium Hydride and Magnesium Fluoride

Abstract: Magnesium is an understudied chemical element that is quite useful in materials science and may be an essential astrochemical building block for grain formation in proto-planetary disks. This work provides quantum chemical prediction for the vibrational and rovibrational spectra of the structurally similar magnesium hydride and magnesium fluoride monomers and dimers. Magnesium fluoride is commonly utilized in infrared-observing windows and is a known terrestrial mineral, sellaite. Magnesium hydride is likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Such has been proposed as a means of computing vibrational frequencies and other spectroscopic values, but results have been mixed. However, recent work has shown that CCSD(T)‐F12b with a triple‐zeta basis set may achieve a nice Pauling point for a cancellation of errors generating fundamental vibrational frequencies that are closely coincident with much more costly CcCR QFF VPT2 results . However, the reliability of such an overlap has not been systematically documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such has been proposed as a means of computing vibrational frequencies and other spectroscopic values, but results have been mixed. However, recent work has shown that CCSD(T)‐F12b with a triple‐zeta basis set may achieve a nice Pauling point for a cancellation of errors generating fundamental vibrational frequencies that are closely coincident with much more costly CcCR QFF VPT2 results . However, the reliability of such an overlap has not been systematically documented.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work has shown that CCSD(T)-F12b with a triple-zeta basis set may achieve a nice Pauling point for a cancellation of errors generating fundamental vibrational frequencies that are closely coincident with much more costly CcCR QFF VPT2 results. [29][30][31] However, the reliability of such an overlap has not been systematically documented. This work will do just that comparing CCSD(T)-F12 QFF results (as well as those from MP2-F12) with those from both previous CcCR values and those from experiment where available.…”
mentioning
confidence: 99%
“…The diatomic species that contain these bonds have an equal number of valence electrons occupying bonding and antibonding orbitals, which yields a bond order of 0, meaning that bond formation is not energetically favorable much like that present in noble gas dimers. Additionally, group 2 elements prefer 180°bond angles implying a strong preference for the valence electrons to be found on opposite sides of the atoms (Bassett and Fortenberry, 2018;Palmer and Fortenberry, 2018;Doerksen and Fortenberry, 2020;Watrous et al, 2021). In returning to the bond lengths, the Be Be, Be Mg, and Mg Mg bonds are close to the sum of their constituent atom's Van der Waals radii rather than their covalent radii.…”
Section: Resultsmentioning
confidence: 97%
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The geometries are optimized with coupled cluster singles, doubles, and perturbative/parenthetical triples [CCSD(T)] [45] with the augcc-pV5Z basis set. [46][47][48] The reader should note that all computations for the argon atom contain the additional ðX þ dÞ orbitals. This minimum structure is then refined with geometrical considerations for the nuclear response to core electrons in the wavefunction through CCSD(T) geometry optimizations with the Martin-Taylor (MT) correlating basis set [49] .…”
Section: Computational Detailsmentioning
confidence: 99%
“…The same procedure utilized to produce rotational constants to within 30 MHz and vibrational frequencies to within 5 cm −1 and sometimes even 1 cm −1 will be utilized here . The geometries are optimized with coupled cluster singles, doubles, and perturbative/parenthetical triples [CCSD(T)] with the aug‐cc‐pV5Z basis set .…”
Section: Computational Detailsmentioning
confidence: 99%